Higher education and COVID-19: An overview of the most important challenges - Mahdieh Motie; Seyed Meysam Mousavi; Zahra Sarabandi; Reza Dehnavieh; Khalil Kalavani (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
The COVID-19 pandemic has caused many disruptions in face-to-face learning, and the use of distance learning has affected all students and teachers [1]. There are a few quantitative studies conducted on the consequences of the COVID-19 virus and its impact on indoors environments such as university. In indoors environments with low ventilation, the virus has the capacity to linger for longer before being inhaled or falling to a surface, which could result in transmission. In enclosed environments, low humidity, air conditioning, and low UV light may all contribute to longer survival of viral particles.